2020
DOI: 10.1111/iere.12419
|View full text |Cite
|
Sign up to set email alerts
|

Urban Population and Amenities: The Neoclassical Model of Location

Abstract: We develop a neoclassical general equilibrium model to explain cross‐metro variation in population and density. We provide new methods to estimate traded and nontraded productivities, and elasticities of housing and land supply, using density and land area data. From wage and housing cost indices, the model explains half of U.S. density and population variation and finds that quality of life determines location choices more than trade productivity; productivity and factor substitution in housing matter most, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…An improvement in amenities generates "direct," "misallocation," and "price" effects, where the elasticity of housing supply determines the magnitude of the "misallocation" and "price" effects. 12 In general, when both TFP and amenities of a given city change, the resulting change in aggregate welfare is given by (15) ΔV ∝ Δ (…”
Section: Intuitionmentioning
confidence: 99%
See 1 more Smart Citation
“…An improvement in amenities generates "direct," "misallocation," and "price" effects, where the elasticity of housing supply determines the magnitude of the "misallocation" and "price" effects. 12 In general, when both TFP and amenities of a given city change, the resulting change in aggregate welfare is given by (15) ΔV ∝ Δ (…”
Section: Intuitionmentioning
confidence: 99%
“…However, the effect of local TFP on 11 We substitute the expression for the nominal wage (5) into the labor demand equation 2. 12 The direct effect of better amenities on aggregate utility is given by Z i…”
Section: Intuitionmentioning
confidence: 99%
“…Second, there are agglomeration spillovers between workers in the two regions that themselves may also depend on the transportation cost. Because it is set up to be calibrated primarily using quantities rather than prices, this model resembles Albouy and Stuart (2020) in some ways, though it considers the spatial equilibrium within rather than between metro areas.…”
Section: Modelmentioning
confidence: 99%
“…Graves (1983) found that the residents of the United States first valued income when choosing a city, but when the income increased, they would move to a city with higher amenity. Albouy et al (2020) found that amenities determine location more than trade productivity in the United States; urban amenities can also be provided by the private sector, such as coffee shops, etc. Glaeser et al (2001) believed that urban economics traditionally regarded the city as a place with advantages in production and disadvantage in consumption, but the importance of the city is increasingly reflected in becoming a consumption center.…”
Section: Introduction 11mentioning
confidence: 99%